Coligand Promoted Controlled Assembly of Hierarchical Heterobimetallic Nitroprusside Based Aggregates1. Issue 14 (14th October 2014) - Dey, Mamon; Sarma, Bipul; Gogoi, Nayanmoni
Abstract The possibility to control the aggregation pattern of a seven coordinate Mn2+ complex formed by 2, 6‐diacetylpyridine bis(benzoyl hydrazone) (dapbh) with sodium nitroprusside was explored. The results presented in this manuscript show that variation of the reaction conditions triggers remarkable deviation in the architecture of charge mediated self‐assemblies formed by the seven coordinate Mn2+ complex with nitroprusside anion. KSCN as coligand has a profound impact on the self‐assembly process.